Japan in world history - Huffman, James L. (New York : Oxford University Press, 2010)
"Here is a marvelous compact history of Japan from earliest times to the present focusing on Japan's relationships with the rest of the world. In lively prose rooted in observations by people who lived the history, the work highlights the contributions of a wide range of acetors: women as well as men, commoners as well as elites"--Publisher supplied summary.
Before the brush (to 645 ce) -- Emperors and aristocrats : rule by law and taste (645-1160) -- Warriors : the long rise (1160-1550) -- Peace and its benefits (1550 to 1850) -- The nation transformed (1850 to 1905) -- Engaging the world, for good and for ill (1905 to 1945) -- A new kind of power (after 1945).
Sadrži bibliografske bilješke i kazalo
Keywords: svjetska povijest -- japanska povijest; Japan - vanjskopolitički odnosi